Reward management and job satisfaction among health workers employees in Al-Medina region, (2023) Cross-Sectional Survey - Alsuhaymi, Essa Burayk A; Almutairi, Mohammed Hamed M; Alkhaibri, Umran Mohammed U; Aljohani, Talal Saleh A; M Alharbi, Hamoud Mohammed; Al -Rashidi, Nasser Ayed Musleh; S Almalki, Fahad Mohammed; Alalawi, Saud Marzoq; F Almutairi, Abdulrahim Qayid; Alraddadi, Salman Awadh (Migration Letters, 2024)
Choosing appropriate incentives and benefits for staff members has always been a challenge for those in charge of human resource management. This study’s sample population consisted of health care personnel who were employed by the Ministry of Health in Madinah and Saudi Arabia’s hospitals and primary healthcare centers. 285 questionnaires were sent online to participants, of which 192 were collected for analysis. During the course of this investigation, four possibilities were considered and examined. The findings showed that rewards, both financial and nonfinancial, have a positive and substantial association with job satisfaction; financial rewards had a correlation of 0.819, while nonfinancial rewards had a correlation of 0.740. According to the findings of the regression analysis, financial rewards (with a coefficient of determination of 0.597) have a more significant bearing on levels of job satisfaction than do non-financial rewards (with a coefficient of determination of 0.438).